2008
DOI: 10.1021/jf800142q
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Kinetics of the Antiradical Probe 2,2-Diphenyl-1-picrylhydrazyl in Methanol and Acetonitrile by the Antiradical Activity of Protocatechuic Acid and Protocatechuic Acid Methyl Ester

Abstract: This work evaluates the reduction kinetics of the antiradical probe 2,2-diphenyl-1-picrylhydrazyl (DPPH (*)) in methanol and acetonitrile by the antiradical activity of protocatechuic acid (3,4-dihydroxybenzoic acid, 1) and protocatechuic acid methyl ester ( 2). The reduction kinetics of DPPH (*) in both solvents by the antiradical activity of the p-catechol group in 2 is regular, that is, coincide with the proposed standard kinetic model for the reduction kinetics of DPPH (*) by the antiradical activity of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The better antioxidant performance of catechin than luteolin in acetone was in line with those studies considering the reducing 2–H (Kondo et al., ) and 3–OH (Fujisawa et al., ) groups in flavanols more effective than the electron‐withdrawing 1,4‐pyrone moiety in flavones to donate a hydrogen atom from the catecholic –OH groups in the B ring (Leopoldini et al., ; Zhang et al., ). Electron‐withdrawing groups in nonalcoholic solvents strongly decrease the tendency of the p ‐catechol to transfer one hydrogen atom to DPPH ● (Sentandreu, Navarro, & Sendra, ). Gaikwad, Barik, Priyadarsini, and Rao () found that electron‐donating substituents considerably enhance the antioxidant activity in different solvents used in DPPH ● scavenging activity assay.…”
Section: Resultsmentioning
confidence: 99%
“…The better antioxidant performance of catechin than luteolin in acetone was in line with those studies considering the reducing 2–H (Kondo et al., ) and 3–OH (Fujisawa et al., ) groups in flavanols more effective than the electron‐withdrawing 1,4‐pyrone moiety in flavones to donate a hydrogen atom from the catecholic –OH groups in the B ring (Leopoldini et al., ; Zhang et al., ). Electron‐withdrawing groups in nonalcoholic solvents strongly decrease the tendency of the p ‐catechol to transfer one hydrogen atom to DPPH ● (Sentandreu, Navarro, & Sendra, ). Gaikwad, Barik, Priyadarsini, and Rao () found that electron‐donating substituents considerably enhance the antioxidant activity in different solvents used in DPPH ● scavenging activity assay.…”
Section: Resultsmentioning
confidence: 99%
“…However, PCA esters have higher antioxidant activity than PCA likely because of the higher lipophilicity, which is a main factor in counteracting lipoperoxidation [89,90]. It has been demonstrated that the radical scavenging activities of PCA and its esters depend on the solvent used [91,92]. In non-alcoholic acetone or acetonitrile PCA and its esters consume two radicals and are converted to the corresponding quinones.…”
Section: Antioxidant Activity Of Pcamentioning
confidence: 99%
“…DPPH • is a stable nitrogen‐centered free radical whose color changes from violet to yellow upon reduction by the process of hydrogen donation. The main principle of this assay is based on the reduction of DPPH • to DPPH‐H in the presence of a hydrogen‐donating antioxidant to form yellow‐colored diphenylpicrylhydrazine . It has been reported that antioxidants such as ascorbic acid, polyphenols, flavonoids and glutathione can scavenge DPPH • via hydrogen‐donating behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The main principle of this assay is based on the reduction of DPPH • to DPPH-H in the presence of a hydrogen-donating antioxidant to form yellow-colored diphenylpicrylhydrazine. 31 It has been reported that antioxidants such as ascorbic acid, polyphenols, flavonoids and glutathione can scavenge DPPH • via hydrogen-donating behavior. DPPH • is commonly used to evaluate the free radical-scavenging activities of natural products.…”
Section: Antioxidant Activitymentioning
confidence: 99%